2011
DOI: 10.1007/s00426-011-0378-8
|View full text |Cite|
|
Sign up to set email alerts
|

Correlations between spatial compatibility effects: are arrows more like locations or words?

Abstract: Responses are more efficient when their spatial mappings with features of targets are compatible compared to when they are incompatible, even when those features are irrelevant to task performance. Currently, a debate exists as to whether spatial information conveyed by different stimulus modes leads to qualitatively different spatial representations. We investigated the relations between three of the most commonly used spatial stimulus modes-arrows, locations, and location words-using correlations of compatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 34 publications
3
27
1
Order By: Relevance
“…Also, Wiegand and Wascher (2005) explained the quickly fading horizontal Simon effect with the automatic translation of horizontal stimulus code into corresponding motor activation via the dorsal stream of the cortical visual system, and they explained the vertical Simon effect's increase over time with the more time-consuming cognitive translation of the vertical stimulus location code into a corresponding vertical response activation code within the ventral stream of the cortical visual system. In addition, recent studies that investigated the time course of Simon effects based on irrelevant word meaning consistently showed an increasing Simon effects over time, even if horizontal word meaning and left-right manual responses were used (Miles & Proctor, 2009, 2012Pellicano et al, 2009;Proctor et al, 2009;Vu & Proctor, 2011). On the basis of these findings, our expectations about different time-dependent developments of Simon effects for vertical vs. horizontal saccades might appear unjustified.…”
Section: Methodsmentioning
confidence: 58%
“…Also, Wiegand and Wascher (2005) explained the quickly fading horizontal Simon effect with the automatic translation of horizontal stimulus code into corresponding motor activation via the dorsal stream of the cortical visual system, and they explained the vertical Simon effect's increase over time with the more time-consuming cognitive translation of the vertical stimulus location code into a corresponding vertical response activation code within the ventral stream of the cortical visual system. In addition, recent studies that investigated the time course of Simon effects based on irrelevant word meaning consistently showed an increasing Simon effects over time, even if horizontal word meaning and left-right manual responses were used (Miles & Proctor, 2009, 2012Pellicano et al, 2009;Proctor et al, 2009;Vu & Proctor, 2011). On the basis of these findings, our expectations about different time-dependent developments of Simon effects for vertical vs. horizontal saccades might appear unjustified.…”
Section: Methodsmentioning
confidence: 58%
“…Most findings are that the location-based Simon effect is largest for fast responses but decreases, and even may reverse, as responses slow when the imperative stimulus is displayed in a left or right location (Ansorge & Wühr, 2004;Ellinghaus, Karlbauer, Bausenhart, & Ulrich, 2017;Pratte, Rouder, Morey, & Feng, 2010;Servant, Montagnini, & Burle, 2014;Ulrich et al, 2015). In contrast, the word-and arrow-based Simon effects increase as RTs increase (Miles & Proctor, 2012;Pellicano et al, 2009;Proctor et al, 2009).…”
Section: Response-time Distribution and Chronometric Analysesmentioning
confidence: 99%
“…Some findings suggest that different location modes affect responses with modespecific mechanisms, as the Simon effects based on them seem to have different temporal dynamics. For example, the location-based Simon effect decreases as RTs increase across the RT distribution for a left-or right-displayed imperative stimulus, whereas the word-and arrow-based Simon effects increase as RTs increase (Miles & Proctor, 2012;Pellicano et al, 2009;Proctor et al, 2009). Wascher and colleagues (Wascher, Schatz, Kuder, & Verleger, 2001;Wiegand & Wascher, 2005 suggested that increasing and decreasing delta plots of Simon effects obtained in various tasks are the result of two distinct mechanisms.…”
Section: Mode-specific or Shared Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, consider the study of Miles and Proctor (2012), who examined correlations of Simon compatibility effects obtained with three different types of stimulus materials (i.e., locations, arrows, and words). They found a significant correlation between the compatibility effects obtained with arrows and words, but no correlation between either of these effects and the compatibility effect obtained with location stimuli.…”
Section: What Can Be Concluded From Rt-based Correlations?mentioning
confidence: 99%